Prevalence and factors associated with peripheral neuropathy in a setting of retail pharmacies in Malaysia–a cross-sectional study - Siew, Mooi Ching; Kai, Wei Lee; Yusof Khan, Abdul Hanif Khan; Devaraj, Navin Kumar; Ai, Theng Cheong; Sook, Fan Yap; Fan, Kee Hoo; Wan Sulaiman, Wan Aliaa; Wei, Chao Loh; Shen, Horng Chong; Patil, Mansi; Ramachandran, Vasudevan (Public Library of Science, 2024)
Peripheral neuropathy is a common cause for neurological consultation, especially among those with diabetes mellitus. However, research on peripheral neuropathy among the general population is lacking in Malaysia. This study aimed to determine the prevalence and factors associated with peripheral neuropathy in a setting of retail pharmacies. This cross-sectional study of 1283 participants was conducted at retail pharmacies in Selangor. Peripheral neuropathy was defined as the final score in the mild to severe category in the severity rating scale using a biothesiometer. SPSS version 26 was used to perform the analysis. Multiple logistic regressions were used to determine the factors associated with peripheral neuropathy. The prevalence of peripheral neuropathy based on the biothesiometer was 26.5%. According to multiple logistic regression, the predictors of peripheral neuropathy were those who have diabetes (AOR = 3.901), aged more than 50 years (AOR = 3.376), have secondary education or below (AOR = 2.330), are male (AOR = 1.816), and have underlying hypertension (AOR = 1.662). Peripheral neuropathy is a reasonably prevalent condition, affecting a quarter of the general population, and often goes undiagnosed. It is crucial for healthcare providers to proactively screen for peripheral neuropathy, particularly in high-risk populations, to prevent potential complications.